Q. 124.7( 11 Votes )

Find that non-zer

Answer :

(k + 1)x2-2(k-1)x + 1 = 0

This is a quadratic equation of form ax2 + bx + c = 0


Where a = k + 1, b = -2(k-1), c = 1


For equal roots, D = 0


D = b2-4ac = 0


Substituting the values of a, b and c


(-2(k-1))2-4(k + 1)(1) = 0


4(k2 + 1-2k)-4k-4 = 0


4k2-12k = 0


4k(k-3) = 0


There are two possible values of k, k = 0 and k = 3


We neglect k = 0 as on putting k = 0; the equation does not remain quadratic.


k = 3 is our required value of k.


Now,



As we know roots are equal,


Therefore, each root =


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses